Life-Threatening Hemoptysis - Deshwal, Himanshu; Sinha, Ankur; Mehta, Atul C. (Seminars in Respiratory and Critical Care Medicine, 2020)
Life-threatening hemoptysis (LTH) is any amount of hemoptysis that causes significant hemodynamic decompensation or respiratory distress which may lead to death if left untreated. While the amount of hemoptysis that qualifies as massive hemoptysis has continued to be debated, any amount between 100 to 1,000 mL/day is considered significant. Up to 15% cases of hemoptysis are LTH and need urgent life-saving intervention. Understanding of pulmonary vascular anatomy is of paramount importance to manage LTH. The goal of treatment lies in airway protection, appropriate oxygenation, and prevention of exsanguination. Once the airway is stabilized, a quick diagnosis and control of bleeding site is targeted. This chapter highlights current practices and approach to LTH including medical management, bronchoscopic approach, and advanced therapies such as bronchial artery embolization and surgical resection. We review situations, such as bronchiectasis, vascular malformation, diffuse alveolar hemorrhage, and tracheostomy bleed and specific approach to management of these conditions in a systematic and evidence-based manner.
Keywords: life-threatening hemoptysis; bronchoscopy; bronchiectasis; tracheostomy bleed; diffuse alveolar hemorrhage